On dependability metrics for wireless industrial communications-applied to IEEE 802.11ax - Trabl, Andreas; Scheuvens, Lucas; Hobler, Tom; Franchi, Norman; Fettweis, Gerhard P. (IEEE 5G World Forum, 5GWF 2019 - Conference Proceedings, 2019)
Wireless communications solutions allow to exchange data in a flexible and cheap manner, especially in industrial use cases, which experience an increasing attraction in the context of 5G. However, high demands towards latency and dependability, especially for closed-loop control purposes, still prevent the wide deployment in these scenarios. Studies on specific opportunities and limitations of potential technologies are still lacking. In this paper we present a simulative dependability analysis of the upcoming WLAN standard IEEE 802.11ax for industrial use cases. Small-scale fading as well as system noise are considered as error sources. State-of-the-art is a dependability analysis by means of packet error ratios. However, such a ratio is not able to reflect application demands precisely. Thus, in this paper a dependability analysis is carried out based on the recently proposed metrics reliability and availability. For applications able to handle a certain number of consecutive packet errors, two new metrics are proposed, i.e., application reliability and application availability. It is shown that applications utilizing closed-loop control can achieve a vast dependability gain when tolerating packet errors. The gain is higher in cases when bursts of packet errors occur rarely. We conclude that IEEE 802.11ax has a promising dependability for different applications for middle to high SNRs.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Availability; Closed-loop control; IEEE 802.11ax; Industrial radio; Reliability; Wireless industrial communications